Development of an AI‐based support system for controlled ovarian stimulation - Yoshimasa Asada; Tomoya Shinohara; Sho Yonezawa; Tomoki Kinugawa; Emiko Asano; Masae Kojima; Noritaka Fukunaga; Natsuka Hashizume; Yoshiki Hashiba; Daichi Inoue; Rie Mizuno; Masaya Saito; et al. (Reproductive Medicine and Biology)
Abstract Purpose Controlled ovarian stimulation (COS) is vital for IVF. We have developed an AI system to support the implementation of COS protocols in our clinical group. Methods We developed two models as AI algorithms of the AI system. One was the oocyte retrieval decision model, to determine the timing of oocyte retrieval, and the other was the prescription inference model, to provide a prescription similar to that of an expert physician. Data was obtained from IVF treatment records from the In Vitro Fertilization (IVF) management system at the Asada Ladies Clinic, and these models were trained with this data. Results The oocyte retrieval decision model achieved superior sensitivity and specificity with 0.964 area under the curve (AUC). The prescription inference model achieved an AUC value of 0.948. Four models, namely the hCG prediction model, the hMG prediction model, the Cetrorelix prediction model, and the Estradiol prediction model included in the prescription inference model, achieved AUC values of 0.914, 0.937, 0.966, and 0.976, respectively. Conclusion The AI algorithm achieved high accuracy and was confirmed to be useful. The AI system has now been implemented as a COS tool in our clinical group for self‐funded treatments.